Finding Our Way with Native Literature (2020-02-07) - Meland, Carter; University of Minnesota Duluth. Department of American Indian Studies (2020)
FEB 7TH 2-3PM, CINA HALL 106; Free and open to the public In this presentation, novelist Carter Meland talks about the transformative power of Native literatures and what they mean to him as a teacher, a creative writer, and an Anishinaabe descendent seeking to make sense of his fractured family history.